First Radiobiological Characterization of Skin and Bone Cells from A Patient Suffering from the PI3KCA-Related Overgrowth Spectrum (PROS) Syndrome - Bachelet, Jean-Thomas; Granzotto, Adeline; Ferlazzo, Mélanie; Sonzogni, Laurène; Berthel, Elise; Devic, Clément; Foray, Nicolas (Archives of Clinical and Medical Case Reports, 2020)
The phosphatidylinositol 3-kinase catalytic subunit (PI3KCA) is an oncogene involved in the control of cellular proliferation. Some somatic mosaic heterozygous mutations of PI3KCA are associated with overgrowth malformations in skin, vasculature, bones, fat or brain tissues, gathered under the common term of “PI3KCA-related overgrowth spectrum” (PROS) syndromes. Since PROS patients may be exposed to ionizing radiation through anti-tumor radiotherapy and radiodiagnosis, the evaluation of the radiation-induced risk potentially linked to PROS syndrome is needed. However, no radiobiological characterization of this syndrome was available yet. Primary fibroblast and osteoblast cell lines derived from a PROS patient were exposed to radiation in realistic conditions. The PROS patient cells appeared to be associated with a moderate but significant radiosensitivity, a delayed radiation-induced nucleoshuttling of the ATM kinase, and an impairment of DNA double-strand breaks repair and signaling. Such phenotype may be partially corrected by using bisphosphonates combined with statins, which renders cells more radioresistant. Our data suggest that the PI3KCA protein may contribute to the individual Archives of Clinical and Medical Case Reports 1053 radiation response, as an ATM substrate. Furthermore, our findings suggest that exposure to radiation of PROS patients should be therefore justified carefully.